Improvement of renal function after transcatheter aortic valve replacement in patients with chronic kidney disease. - Michel V Lemes da Silva (Public Library of Science (PLoS), 2021)
Background Chronic kidney disease is commonly found in patients with aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR) and has marked impact in their prognosis. It has been shown however that TAVR may improve renal function by alleviating the hemodynamic barrier imposed by AS. Nevertheless, the predictors of and clinical consequences of renal function improvement are not well established. Our aim was to assess the predictors of improvement of renal function after TAVR. Methods The present work is an analysis of the Brazilian Registry of TAVR, a national non-randomized prospective study with 22 Brazilian centers. Patients with baseline renal dysfunction (estimated glomerular filtration rate [eGFR] < 60mL/min/1.73m2) were stratified according to renal function after TAVR: increase >10% in eGFR were classified as TAVR induced renal function improvement (TIRFI); decrease > 10% in eGFR were classified as acute kidney injury (AKI) and stable renal function (neither criteria). Results A total of 819 consecutive patients with symptomatic severe AS were included. Of these, baseline renal dysfunction (estimated glomerular filtration rate [eGFR] < 60mL/min/1.73m2) was present in 577 (70%) patients. Considering variance in renal function between baseline and at discharge after TAVR procedure, TIRFI was seen in 197 (34.1%) patients, AKI in 203 (35.2%), and stable renal function in 177 (30.7%). The independent predictors of TIRFI were: absence of coronary artery disease (OR: 0.69; 95% CI 0.48-0.98; P = 0.039) and lower baseline eGFR (OR: 0.98; 95% CI 0.97-1.00; P = 0.039). There was no significant difference in 30-day and 1-year all-cause mortality between patients with stable renal function or TIRFI. Nonetheless, individuals that had AKI after TAVR presented higher mortality compared with TIRFI and stable renal function groups (29.3% vs. 15.4% vs. 9.5%, respectively; p < 0.001). Conclusions TIRFI was frequently found among baseline impaired renal function individuals but was not associated with improved 1-year outcomes.